Evaluation on Thermo-Electrical Characteristics of Sio2 Nanofluids for Fuel Cell Cooling Application in Automobiles - Akilu, Suleiman; Tesfamichael Baheta, Aklilu; V. Sharma, K (International Journal of Engineering and Technology, 2018)
Effective thermal management is critical requirement in fuel cell technologies to avoid the performance degradation during operation. Nanofluids offer the potential to address this cooling challenge in fuel cells better than pure fluids. However, due to the electrochemical changes associated with the proton exchange membrane system, a strict limit on thermal and electrical properties of coolant needs to comply. In this study, the thermal and electrical conductivities of silicon dioxide (SiO2) dispersion of ethylene glycol (EG), glycerol (G), and 40:60 by mass ethylene glycol-glycerol (EG/G) was investigated experimentally. Measurements were carried for particle volume concentrations of 0.25â€“2.0% at a temperature of 30 Â°C. The thermal and electrical conductivity of the nanofluids significantly increases with SiO2 loading. Maximum enhancements of âˆ¼4.0% and âˆ¼198% at a volume concentration of 2.0% were obtained with SiO2-EG/G, respectively. Further, analysis of the results reveals that SiO2/G exhibited the greatest thermo-electrical performance, followed by SiO2-EG/G and EG. Therefore, SiO2-EG/G nanofluid is best-suited coolant for PEM fuel cell thermal applications.Â Â